Implementation of Green Accounting, Internal Corporate Governance Strength, Material Flow Cost Accounting On Sustainable Development: Corporate Social Responsibility as a Moderating Variable - Kadarwati, Mutiara (Riau International Conference on Economics, Business and Accounting, 2025)
Sustainable development is an activity that integrates environmental, social and economic considerations into a development strategy to ensure environmental integrity and safety, efficiency, welfare and quality of life for present and future generations. Sustainable development can be achieved by implementing green accounting, internal corporate governance strength, and material flow cost accounting. This research examines the impact of green accounting, internal corporate governance strength, and material flow cost accounting on sustainable development, with corporate social responsibility (CSR) as a moderating variable. Sustainable development integrates environmental, social, and economic considerations, aiming to ensure quality of life and environmental integrity for current and future generations. The study focuses on textile and garment companies listed on the Indonesia Stock Exchange from 2019 to 2021, with a purposive sample of 60 firms analyzed using Partial Least Squares (PLS). Findings indicate that green accounting, internal corporate governance strength, and material flow cost accounting positively influence sustainable development. Furthermore, CSR strengthens the positive effects of green accounting and material flow cost accounting on sustainable development, while CSR does not moderate the effect of internal corporate governance strength.